Insights into distinct biocarbon assembly and graphitization derived from large-scale bioresource by integrating machine learning with Raman and XRD spectroscopic profiling - Junsheng Yu; Jing Hong; Yujia Fang; Jiacheng Kang; Zongtai Tang; Lei Zhu; Bing Gao; Ling Luo; Dan Sun; Yanting Wang; Liangcai Peng; Hua Yu (Bioresource Technology, 2026)

Amphiregulin as a central dynamic network biomarker in inhaled polyhexamethylene guanidine triggered pulmonary fibrosis - Jianzhong Zhang; Xin Li; Yuxin Ma; Wanjun Zhang; Zihao Han; Yanting Li; Jiayin Sun; Siqi Wang; Wei Han; Jing Liu; Yuxin Zheng; Jinglong Tang (Journal of Hazardous Materials, 2026)

Extraction, purification and structural characterization of a novel polysaccharide purified from Lentinula sp. and its antioxidant and hypoglycemic activities - Guangpeng Chu; Meizi Piao; Haili Yi; Yanting Sun; Tiejun Chen (Natural Product Research, 2026)

Engineered cytosolic and chloroplastic UDP-glucose epimerases distinctly modulate xylan interplay for size-tunable cellulose nanocrystals production in Oryza sativa - Yumeng Sun; Muzi Li; Meiyun Yang; Wennian Xia; Sha Wang; Zhongyi Wang; Yanting Wang; Liangcai Peng; Huizhen Hu; Ran Zhang (Carbohydrate Polymers, 2026)

Analysis of the effect of LFR bending fuel assembly on thermal–hydraulic characteristics - JiTong Sun; Mei Huang; YaoDi Li; AoNan Li; YanTing Cheng (Annals of Nuclear Energy, 2026)

Magnetic resonance imaging for rapid, noninvasive and accurate assessment of ovarian maturation in live Channa argus (Cantor, 1842) - Wenqian Sun; Weiyin Vivian Liu; Xingyu Chen; Guangcan Lin; Hao Li; Yanting Song; Chengdong Peng; Wen Xiong; Yu Peng; Shangong Wu; Shouqi Xie; Sovan Lek; et al. (Aquaculture, 2026)

Stabilizing photogranule systems under low-light and limited-aeration: From operational strategy to underlying mechanism - Xiaojing Yang; Lan Tang; Jinke Sun; Fahui Ji; Peng Qi; Meng Yan; Yanjuan Luo; Chen Yang; Yanting Lin; Hui Lu (Water Research, 2026)

Enhanced spring precipitation in central Asia induced by ENSO under global warming - Lin Sun; Yanting Zhang; Xiao-Tong Zheng (Climate Dynamics, 2026)

Deciphering the acute toxicity mechanisms of PFAS in algae: A molecular descriptor and binding energy hierarchy perspective - Yanting Li; Lin Zhao; Lu Wang; Han Zhang; Guodong Xing; Jinrui Yuan; Yongkui Yang; Peizhe Sun (Journal of Hazardous Materials, 2025)

Metabolomics analysis reveals the formation mechanism of Cordyceps militaris fruiting bodies in liquid culture - Yihong Sun; Bingjie He; Xuemei Cao; Zimo Li; Lina Xu; Yanting Li; Shang Guo (Food Chemistry, 2025)

Synergistic effect of Cu-Ni bimetallic doping in Cd0.8Zn0.2S for enhanced photocatalytic CO2 reduction: Modulating the d-band center for improved activity - Haonan Li; Keming Li; Shuhan Sun; Yongjia Zhang; Zhanfeng Li; Yanting Tian (Journal of Environmental Chemical Engineering, 2025)

Deacetylase SIRT2 Inhibition Promotes Microglial M2 Polarization Through Axl/PI3K/AKT to Alleviate White Matter Injury After Subarachnoid Hemorrhage - Kaikun Yuan; Qiaowei Wu; Yanting Yao; Jiang Shao; Shiyi Zhu; Jinshuo Yang; Qi Sun; Junjie Zhao; Jiayi Xu; Pei Wu; Yuchen Li; Huaizhang Shi (Translational Stroke Research, 2025)

Exploration into the Mechanism of Yiyi Baijiang Decoction Attenuating Chronic Pelvic Inflammation Based on Network Pharmacology and Experimental Verification - Yanting Wei; Hongning Su; Jiajia Li; Wenli Zheng; Lili Li; Miao Zhou; Yimeng Sun (Biochemical Genetics, 2025)

Halomonas fermentation promoted the biotransformation of active substances from Dictyophora indusiata pileus and the enhancement of antioxidant capacity - Xueying Zheng; Ying He; Lei Ma; Yanting Sun; Jiazi Yu; Zeguo Feng; Censhu Li; Jiaru Jiang; Xiaoni Zhang; Liguo Qin; Dan Tan; Yali Zhang (Food Bioscience, 2025)

Long-term field observations of the impacts of drought and stand development on runoff in a forested watershed - Shulan Sun; Wenhua Xiang; Zhonghui Zhao; Xiangwen Deng; Shuai Ouyang; Liang Chen; Yanting Hu; Yelin Zeng; Changhui Peng (Agricultural and Forest Meteorology, 2025)

A large-scale integrated transcriptomic atlas for soybean organ development - Jingwei Fan; Yanting Shen; Chuan Chen; Xi Chen; Xiaoyue Yang; Haixia Liu; Ruiying Chen; Shulin Liu; Bohan Zhang; Min Zhang; Guoan Zhou; Yu Wang; et al. (Molecular Plant, 2025)

Vibroacoustic Response of a Disc-Type Underwater Glider During Its Entry into Water - Zhaocheng Sun; Yanting Yu; Dong Li; Chuanlin He; Yue Zhang (Journal of Marine Science and Engineering, 2025)
Underwater gliders are extensively employed in oceanographic observation and detection. The structural characteristics of thin-wall shells are more susceptible to vibrations from internal mechanical components; this noise emission becomes more complex with the presence of water surfaces. The finite element method (FEM) is introduced to discuss the dynamic performance of cylindrical shells with different lengths. The acoustic-structure coupling, together with the effect of the water surface, is validated by comparisons with experimental or analytical solutions under three cases: half-filled, half-submerged, and partially submerged in fluid. Compared to the verification result, the relative error of the eigenfrequency derived from the numerical result is less than 3%, and then the mesh division and boundary conditions are adjusted to calculate the vibroacoustic response of a disc-type glider. During its water entry process, there are six distinct bright curves in frequency–depth spectra of sound pressure radiated from a partially immersed disc-type glider. The first curve is continuous, while the remaining five curves display discontinuities around a region where the geometric curvature changes gradually. As the submerged depth increases, this causes a shift in the resonance frequencies, evidenced by the curves transitioning from higher to lower frequencies.

OncomiR mdv1-miR-M7-5p promotes avian lymphomatosis by modulating the BCL2/Bax mitochondrial apoptosis signaling pathway - Jun Zhou; Fan Yang; Congsen Zheng; Yanting Chen; Meiting Chen; Qiaoer Lin; Chuanzhe Chang; Shikai Cai; Zhaoyang Sun; Hua Li; Limei Qin; Yanfeng Chen (Veterinary Microbiology, 2025)

Molecular mechanisms of Lycii Fructus (Goji berries) against xanthine dehydrogenase in hyperuricemia management: Integrating computational, metabolomic, and experimental approaches - Shuxuan Yang; Qinghong Chen; Yanting You; Chuanghai Wu; Meilin Chen; Angela Wei Hong Yang; Xiaomin Sun; Andrew Hung; Xiaoshan Zhao; Hong Li (Food Research International, 2025)

Analysis of zirconium hydride moderator effect on the micro lead-based reactor - Yanting Sun; Xiaoliang Zou; Zhijie Qin; Shichao Zhang (Annals of Nuclear Energy, 2025)

Insights into contrastive cellulose nanofibrils assembly and nanocrystals catalysis from dual regulations of plant cell walls - Yuanhang Ai; Hailang Wang; Peng Liu; Hua Yu; Mengdan Sun; Ran Zhang; Jingfeng Tang; Yanting Wang; Shengqiu Feng; Liangcai Peng (Science Bulletin, 2024)

Impacts of conversion of cropland to grassland on the C-N-P stoichiometric dynamics of soil, microorganisms, and enzymes across China: A synthesis - Ying Li; Jianhui Sang; Canwei Zou; Qingping Zhang; Qian Yang; Gang Xu; Dong-Gill Kim; Matthew D. Denton; Carmen Rosa Carmona; Hongyang Zhao; Yanting Mao; Liping Mao; et al. (CATENA, 2024)

Balancing Water Yield and Water Use Efficiency Between Planted and Natural Forests: A Global Analysis - Shulan Sun; Wenhua Xiang; Shuai Ouyang; Yanting Hu; Changhui Peng (Global Change Biology, 2024)
Climate warming is projected to affect hydrological cycle in forest ecosystems and makes the forest–water relationship more controversial. Currently, planted forests are gaining more public attention due to their role in carbon sequestration and wood production relative to natural forests. However, little is known about how the global patterns and drivers of water yield and water‐use efficiency (WUE) differ between planted and natural forests. Here, we conduct a global analysis to compare water yield and WUE in planted and natural forests using 946 observations from 112 published studies. The results showed that global average water yield coefficient was 0.29 for planted forests and 0.34 for natural forests. Planted forests exhibited lower water yield coefficient ( p p p −1 can maximize the water yield and WUE in planted and natural forests. Water yield coefficient in planted forests was primarily controlled by the factors related to tree growth (i.e., tree height, DBH), while that of natural forest mainly affected by stand structure (i.e., LAI, stand density, DBH). WUE in planted forest was more sensitive to climate than in natural forests. This work highlights the critical role of natural forests in water supply and the importance of tree species selection and stand management (e.g., stand density adjustment) in plantations in future forest restoration policies and climate change mitigation.

Panax quinquefolius saponins and panax notoginseng saponins attenuate myocardial hypoxia-reoxygenation injury by reducing excessive mitophagy - Junyan Xia; Cong Chen; Yanan Sun; Sinai Li; Yuxuan Li; Bai-Ru Cheng; Yanting Pang; Yan Li; Dong Li; Qian Lin (Cell Biochemistry and Biophysics, 2024)

Analytical evaluation of stress–strain behavior of rubberized concrete incorporating waste tire crumb rubber - Xiaoyan Han; Shanshan Zhou; Aijiu Chen; Lingyun Feng; Yanting Ji; Zhihao Wang; Sheng Sun; Keliang Li; Xiaozhou Xia; Qing Zhang (Journal of Cleaner Production, 2024)

Geochemical behavior of C, N, and S in sediments of Hangzhou Bay, Southeastern China: implications for the study of paleoclimate and sea-level changes - Qin Gao; Alexander M. Piotrowski; Zilong Li; Pei Sun Loh; Cuicui Han; Zixuan Wang; Shihang Yang; Zengqing Guo; Dongqin Huang; Yanting Chen (Frontiers in Marine Science, 2024)
The correlation between the amount of organic carbon (OC) and sulfur (S) in sediments has been widely used as a paleosalinity indicator to distinguish between marine and freshwater environments. However, whether the ratio of total OC to total S (TOC/TS) can be used to identify unsteady or dynamic marine environments across sedimentary strata is still contended. An HZW1907 sediment core of 80 m in length was successfully collected in the middle of Hangzhou Bay (HZB), serving as one of the few boreholes that are crucial for the study of geologic and geo-environment changes in the coastal regions of eastern China since the Last Glacial Maximum (LGM). Total OC (TOC), stable carbon isotope, and TS of 82 subsamples from the HZW1907 core were analyzed to reconstruct the history of the shallow water biological pump and sulfur preservation record in the bay since the Late Pleistocene. Our results indicate that the samples had low concentrations of TOC (0.21%) and total nitrogen (TN) (0.02%), high mass ratio of TOC/TN (10.8), low δ 13 C (−24.9‰), low TS content (0.06%), and a high ratio of TOC/TS (9.1) from 33.6 ka BP to 12.3 ka BP, implying that freshwater organic matter (OM), algae, and C3 plant fragments were the main sources of OM in a relatively cold environment. The abundances of TOC, TN, and TS increased to 0.56%, 0.07%, and 0.4%, respectively, while δ 13 C (−23.9‰) increased and TOC/TS (2.7) decreased in the Holocene sediments, suggesting that seawater began to influence the composition of the sediments of HZB. Climate warming, which is likely to have impacted the results, was experienced from 12.3 ka BP. An OC isotope mixing model indicated that since the Mid-late Holocene, more than 70% of riverine OM accounted for the total OM. The TOC/TS ratio was identified as an effective indicator of seawater intrusion, with C/S ratios of 1–6 being considered to indicate a “sea–land transitional zone” sedimentary environment, a C/S >6 indicating freshwater, and a C/S<1 indicating normal marine facies. These findings provide crucial evidence for using TOC/TS to distinguish freshwater from marine environments and enhance our understanding of past climate changes. Therefore, these geochemical indicators can be used in conjunction with other sedimentary records to obtain accurate results about sedimentary evolution.

Assessing the Interactive Effects of High Salinity and Stocking Density on the Growth and Stress Physiology of the Pacific White Shrimp Litopenaeus vannamei - Fei Liu; Jinfeng Sun; Jinnan Long; Lichao Sun; Chang Liu; Xiaofan Wang; Long Zhang; Pengyuan Hao; Zhongkai Wang; Yanting Cui; Renjie Wang; Yuquan Li (Fishes, 2024)
This study was conducted to evaluate the effects of high salinity combined with stocking density on Litopenaeus vannamei. Three salinity gradients, namely, 28 g/L, 36 g/L, and 44 g/L, and two stocking densities, namely, 300 and 600 shrimp/m3, were used to analyze the synergistic effect of high salinity and stocking density on the growth performance, digestibility, and energy budgets of L. vannamei. The experimental testing period lasted 45 days. The research results showed that a salinity level of 36 g/L was the most suitable salinity level for shrimp growth under both high and low stocking densities. The body weight, specific growth rate, and relative weight gain of the shrimp in the 36 g/L salinity group were significantly higher than those in the other two salinity groups under both high and low stocking densities. The high-density farming group with 600 shrimp/m3 exhibited a significant inhibition of shrimp growth compared to the low-density group under the same salinity conditions. The activities of amylase, lipase, and protease in the high-density-group shrimp gradually decreased with an increase in salinity, and the three digestive enzymes had the same overall effect of changing trends. This indicates that under high-density farming conditions, the increase in salinity is not conducive to the digestive function of shrimps. At the same time, the proportion of respiratory energy to feeding energy gradually decreased in the high-density group and with the increase in salinity. However, under the same salinity conditions, the higher the stocking density, the higher the energy consumed by respiration compared to the low-density group. In addition, the expression of the growth-related gene’s small nuclear ribonucleoprotein polypeptide G (SNRPG) under high stocking density was significantly lower than that in the low-density group at a salinity of 28 g/L, and ribosomal protein L7 (RPL7) expression was also significantly lower under high stocking density than that in the low-density group at a salinity of 44 g/L. The expression levels of molting-related genes retinoid X receptor (RXR), ecdysone receptor (ECR), and ecdysone-induced protein 75 (E75) were significantly higher in the 36 g/L salinity group compared with the other two salinity groups under high-stocking-density treatment. The findings indicate that the synergistic effects of salinity and stocking density have a significant impact on the growth of L. vannamei, and excessive salinity would inhibit its growth in the process of high-density culturing.

The Antidepressant Effect of Magnolol on Depression-Like Behavior of CORT-Treated Mice - Chi Xu; Jiayu Ye; Yanting Sun; Xiujian Sun; Jing-gen Liu (Journal of Molecular Neuroscience, 2024)

Mesopore-dominated porous carbon derived from confinement-region activation strategy toward high capacitive desalination performance - Bofeng Li; Zhihua Xiao; Yanting Cao; Zhiqing Yu; Yankun Sun; Zechen Li; Yuxian Wang; Zhenfei Gao; Chunming Xu (Fuel, 2023)

Biofortification of health-promoting glucosinolates in cruciferous sprouts along the whole agro-food chain - Mengyu Wang; Yubo Li; Yuhe Yang; Han Tao; Ghazala Mustafa; Fanliang Meng; Bo Sun; Jiansheng Wang; Yanting Zhao; Fen Zhang; Kejun Cheng; Qiaomei Wang (Trends in Food Science & Technology, 2023)

Peptide YY inhibits transcription and replication of hepatitis B virus by suppressing promoter/enhancer activity - Xiaolun Xu; Weiping Zhou; Xing Tian; Zhongjia Jiang; Xuanhe Fu; Jun Cao; Ye Sun; Biao Yang; Xueqian Li; Yanting Li; Chunmeng Zhang; Guangyan Liu (Virus Genes, 2023)

Diesel exhaust particles exposure induces liver dysfunction: Exploring predictive potential of human circulating microRNAs signature relevant to liver injury risk - Lin Xu; Yanting Li; Wanli Ma; Xueying Sun; Rongrong Fan; Yuan Jin; Ningning Chen; Xiaoxiao Zhu; Huan Guo; Kunming Zhao; Jiao Luo; Chuanhai Li; et al. (Journal of Hazardous Materials, 2023)

Effects of ageing time on the properties of polysaccharide in tangerine peel and its bacterial community - Fangfang Yue; Fan Zhang; Qianwen Qu; Chennan Wang; Yanting Qin; Lingling Ma; Yuze Jia; Mohamedelfatieh Ismael; Yishan Jiang; Tianrui Sun; Xin Lü; Xin Wang (Food Chemistry, 2023)

StemAnalysis: An R-package for reconstructing tree growth and carbon accumulation with stem analysis data - Huili Wu; Shulan Sun; David I. Forrester; Jingning Shi; Wenwen Deng; Xiangwen Deng; Shuai Ouyang; Liang Chen; Yelin Zeng; Yanting Hu; Wenhua Xiang (Computers and Electronics in Agriculture, 2023)

Identifying gaps in the ex situ conservation of native plant diversity in China - Jianfei Ye; Zhangjian Shan; Danxiao Peng; Miao Sun; Yanting Niu; Yun Liu; Qian Zhang; Yong Yang; Qinwen Lin; Jin Chen; Renbin Zhu; Yingwei Wang; et al. (Biological Conservation, 2023)

rTRIPLEXCWFlux: An R package for carbon–water coupling model to simulate net ecosystem productivity and evapotranspiration in forests - Shulan Sun; Shuai Ouyang; Yanting Hu; Zhonghui Zhao; Meixian Liu; Liang Chen; Yelin Zeng; Changhui Peng; Xiaolu Zhou; Wenhua Xiang (Environmental Modelling & Software, 2023)

Andrographolide-treated bone marrow mesenchymal stem cells-derived conditioned medium protects cardiomyocytes from injury by metabolic remodeling - Yanting Sun; Hao Xu; Bin Tan; Qin Yi; Huiwen Liu; Jie Tian; Jing Zhu (Molecular Biology Reports, 2023)

Tree-level stomatal regulation is more closely related to xylem hydraulic traits than to leaf photosynthetic traits across diverse tree species - Yanting Hu; Zhihui Sun; Yelin Zeng; Shuai Ouyang; Liang Chen; Pifeng Lei; Xiangwen Deng; Zhonghui Zhao; Xi Fang; Wenhua Xiang (Agricultural and Forest Meteorology, 2023)

How Do Gene Expression Patterns Change in Response to Osmotic Stresses in Kuruma Shrimp (Marsupenaeus japonicus)? - Yuquan Li; Zhihao Zhang; Zhongkai Wang; Zhitong Deng; Ruiyang Zhao; Jinfeng Sun; Pengyuan Hao; Long Zhang; Xiaofan Wang; Fei Liu; Renjie Wang; Yanting Cui (Journal of Marine Science and Engineering, 2022)
Euryhaline crustaceans cope with external salinity changes by mechanisms of osmoregulation. In the current study, we first cloned and confirmed the ORF sequences of the ion-transportation-related genes Na+/K+-ATPase α subunit (NKAα), cytoplasmic carbonic anhydrase (CAc), and V-type H+-ATPase G subunit (VHA-G), and water channels of aquaporins (AQP3, AQP4, and AQP11) from kuruma shrimp (Marsupenaeus japonicus). Further tissue expression patterns showed a higher expression of MjAQP4, MjCAc, MjNKAα, and MjVHA-G in the gills, as well as a higher expression of MjAQP3 and MjAQP11 in the intestine and muscle, respectively. Then, qPCR analysis was used to assess the mRNA expression levels of those osmoregulatory genes in both post-larvae and adult shrimp when they were exposed to acute salinity stress or salinity acclimation. The results revealed significantly decreased expression levels of MjAQP3, MjAQP11, MjNKAα, and MjCAc, and higher expression levels of MjAQP4 and MjVHA-G when the post-larvae shrimp were directly subjected to 10‰ or 50‰ salinity. Moreover, similar expression patterns were also observed in the post-larvae shrimp during the accommodation to 10‰ or 50‰ salinity. As to the adult shrimp, significantly higher expression levels of those genes were observed in the gills after exposure to 10‰ salinity, whereas only the expression levels of MjAQP3, MjAQP11, and MjNKAα were up-regulated in the gills at 40‰ salinity. In contrast, the expression of MjVHA-G was significantly decreased at 40‰ salinity. Finally, during the acclimation to 10‰ salinity, the expression levels of MjAQP3, MjAQP11, and MjNKAα were also significantly elevated, while the expression of MjCAc was significantly decreased in the gills. In addition, the expression levels of MjAQP3, MjAQP4, MjCAc, and MjVHA-G were significantly decreased in the gills during the acclimation to 55‰ salinity. The findings of the study suggest that the examined genes are critical for the adaptation of aquatic crustaceans to changing environmental salinity. Our study lays as the foundation for further research on osmoregulation mechanisms in M. japonicus.

Circulating expression and clinical significance of LncRNA ANRIL in diabetic kidney disease - Yanting Zhu; Lixia Dai; Xiangyou Yu; Xintian Chen; Zhenjiang Li; Yan Sun; Yan Liang; Bing Wu; Qiong Wang; Xiaoming Wang (Molecular Biology Reports, 2022)
Background Long noncoding RNA ANRIL has been found to be involved in the pathogenesis of diabetic kidney disease (DKD) and is expected to be a new target for prevention of DKD. However, the circulating expression and clinical significance of ANRIL in DKD patients is uncertain. This study aims to explore this issue. Methods The study consisted of 20 healthy controls, 22 T2DM patients (normalbuminuria) and 66 DKD patients (grouped as follows: microalbuminuria, n = 23; macroalbuminuria, n = 22 and renal dysfunction, n = 21). The expressions of ANRIL in peripheral whole blood of all participants were measured by RT-qPCR. Results The expression of ANRIL was significantly up-regulated in DKD patients (microalbuminuria, macroalbuminuria and renal dysfunction groups) than that in healthy control group. ANRIL was also over-expressed in macroalbuminuria and renal dysfunction groups in comparison with normalbuminuria group. ANRIL expression was positively correlated with Scr, BUN, CysC, urine β2-MG and urine α1-MG; while negatively correlated with eGFR in DKD patients. In addition, ANRIL was the risk factor for DKD with OR value of 1.681. The AUC of ANRIL in identifying DKD was 0.922, and the sensitivity and specificity of DKD diagnosis were 83.3% and 90.5%, respectively. Conclusion Our results indicated that highly expressed ANRIL in peripheral blood is associated with progression of DKD. Circulating ANRIL is an independent risk factor of DKD and has a highly predictive value in identifying DKD.

Flavonoids improve drought tolerance of maize seedlings by regulating the homeostasis of reactive oxygen species - Baozhu Li; Ruonan Fan; Guiling Sun; Ting Sun; Yanting Fan; Shenglong Bai; Siyi Guo; Shiquan Huang; Jiong Liu; Hui Zhang; Pengtao Wang; Xiaohong Zhu; et al. (Plant and Soil, 2021)
Background and aims As drought threatens the yield and quality of maize ( Zea mays L.), it is important to dissect the molecular basis of maize drought tolerance. Flavonoids, participate in the scavenging of oxygen free radicals and alleviate stress-induced oxidative damages. This study aims to dissect the function of flavonoids in the improvement of maize drought tolerance. Methods Using far-infrared imaging screening, we previously isolated a drought overly insensitivity ( doi ) mutant from an ethyl methanesulfonate (EMS)-mutagenized maize library and designated it as doi57 . In this study, we performed a physiological characterization and transcriptome profiling of doi57 in comparison to corresponding wild-type B73 under drought stress. Results Under drought stress, doi57 seedlings displayed lower leaf-surface temperature (LST), faster water loss, and better performance in growth than B73. Transcriptome analysis reveals that key genes involved in flavonoid biosynthesis are enriched among differentially expressed genes in doi57 . In line with these results, more flavonols and less hydrogen peroxide (H 2 O 2 ) were accumulated in guard cells of doi57 than in those of B73 with the decrease of soil water content (SWC). Moreover, the capacity determined from doi57 seedling extracts to scavenge oxygen free radicals was more effective than that of B73 under the drought treatment. Additionally, doi57 seedlings had higher photosynthetic rates, stomatal conductance, transpiration rates, and water use efficiency than B73 exposed to drought stress, resulting in high biomass and greater root/shoot ratios in doi57 mutant plants. Conclusion Flavonoids may facilitate maize seedling drought tolerance by lowering drought-induced oxidative damage as well regulating stomatal movement.

Mitochondrial fusion protein 2 regulates endoplasmic reticulum stress in preeclampsia - Dandan Sun; Hui Zhu; Ling Ai; Hanbing Wu; Yanting Wu; Jihua Jin (Journal of Zhejiang University-SCIENCE B, 2021)

Nuclear localization signal in TRIM22 is essential for inhibition of type 2 porcine reproductive and respiratory syndrome virus replication in MARC-145 cells - Huiyuan Jing; Ran Tao; Nan Dong; Sufang Cao; Yanting Sun; Wenting Ke; Yang Li; Jinhe Wang; Yan Zhang; Hui Huang; Wang Dong (Virus Genes, 2019)

Factors Affecting Differential Methylation of DNA Promoters in Arsenic-Exposed Populations - Yanting Zhang; Yuanyuan Li; Lanrong Luo; Qian He; Yanhui Gao; Hongqi Feng; Lijun Zhao; Wei Wei; Songbo Fu; Dianjun Sun (Biological Trace Element Research, 2019)

Identification a novel clinical biomarker in early diagnosis of human non-small cell lung cancer - Yanxia Jin; Yajun Yang; Yanting Su; Xiangdong Ye; Wei Liu; Qing Yang; Jie Wang; Xiangning Fu; Yongsheng Gong; Hui Sun (Glycoconjugate Journal, 2019)

Responses of Tree Transpiration and Growth to Seasonal Rainfall Redistribution in a Subtropical Evergreen Broad-Leaved Forest - Yanting Hu; Ping Zhao; Weijun Shen; Liwei Zhu; Guangyan Ni; Xiuhua Zhao; Zhenzhen Zhang; Xingquan Rao; Lei Ouyang; Xiaomin Zeng; Dan Sun; Yongbiao Lin (Ecosystems, 2018)

Zip1, Zip2, and Zip8 mRNA Expressions Were Associated with Growth Hormone Level During the Growth Hormone Provocation Test in Children with Short Stature - Ping Sun; Shifu Wang; Yali Jiang; Yanting Tao; Yuanyuan Tian; Kai Zhu; Haiyan Wan; Lehai Zhang; Lianying Zhang (Biological Trace Element Research, 2013)

Interaction of avian influenza virus NS1 protein and nucleolar and coiled-body phosphoprotein 1 - Chunyu Zhu; Fangliang Zheng; Tingting Sun; Yanting Duan; Jingzhen Cao; Huawei Feng; Lingling Shang; Ying Zhu; Hongsheng Liu (Virus Genes, 2013)